1993
DOI: 10.1016/0014-5793(93)81587-p
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐CD9 monoclonal antibody elicits staurosporine inhibitable phosphatidylinositol 4,5‐bisphosphate hydrolysis, phosphatidylinositol 3,4‐bisphosphate synthesis, and protein‐tyrosine phosphorylation in human platelets

Abstract: Phosphoinositide metabolism elicited by anti-CD9 monoclonal antibody, a well-characterized platelet activator, was studied using acetylsalicylic acid-treated human platelets. TP82, which is an anti-CD9 monoclonal antibody, induced classical phosphatidylinositol4,5-bisphosphate hydrolysis, as monitored by intracellular Ca*' mobilization and phosphatidic acid production, and synthesis of phosphatidylinositol 3,4-bisphosphate, which is a major component of newly-described 3-phosphorylated inositol phospholipids p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

1994
1994
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 48 publications
0
22
0
Order By: Relevance
“…The precise physiological functions of CD9 remain unknown. However, several studies have suggested that CD9 may be involved in cell signaling, 45,46 cell adhesion, 28,29 cell motility, 47 tumor cell metastasis. 42-44,48 -51 Clinical studies on the expression of CD9 in human cancer tissues have shown a the relationship between the reduced expression of CD9 and the aggressive behavior of the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…The precise physiological functions of CD9 remain unknown. However, several studies have suggested that CD9 may be involved in cell signaling, 45,46 cell adhesion, 28,29 cell motility, 47 tumor cell metastasis. 42-44,48 -51 Clinical studies on the expression of CD9 in human cancer tissues have shown a the relationship between the reduced expression of CD9 and the aggressive behavior of the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Although the specific functional role of the tetramembranespanning family is not fully defined, members of this family appear to associate with adhesion molecules and translate adhesive events into a regulation of cellular behavior (Yatomi et al, 1993). One family member, KAI1, is a metastatic suppressor for prostate cancer (Dong et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…The roles of CD9 in regulating adhesion and cell growth are reflected in its noncovalent association with ␤1 integrin, an adhesion molecule (Slupsky et al, 1989;Masellis-Smith and Shaw, 1994), and membraneanchored EGF-like growth factors (Nakamura et al, 1995). Furthermore, activation of CD9 is associated with the hydrolysis of phosphoinositide during platelet activation (Jennings et al, 1990;Yatomi et al, 1993). Another member of the family, TAPA-1, is found in hematolymphoid cells.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that PIP2 hydrolysis in platelets may also be mediated by a tyrosine kinase-activated phospholipase C-gamma [17]. However it is unlikely that staurosporine activated this pathway since it inhibits tyrosine kinase activities [ 171.…”
Section: Discussionmentioning
confidence: 99%